(untitled) (Journal of Human Sciences, 2025)
The prayers required of muslims cannot be performed without purity, and purification is not complete except With absolutely pure water ,or with pure earth as an alternative to it . The ruling differs if the water is pure or Impure ,and treated water ( sewage ) is one of the types of water , and it can be used in life . lf it is treated in an advanced and modern scientific way , chemically and physically ,after purification , filtration and sedimentation , so that the greatest degree of purity and cleanliness that lslam is keen on is achieved , then this water will return to being water suitable for human use , and the parallel role for this will be for the media and culture in convincing people to use this water without embarrassment . from a religious perspective , it is a solution for those who suffer from water problems . lt is also a modern way to provide the required water , especially in remote or desert places , or where water is scarce . lt helps maintain the groundwater level , and contributes to irrigation and reclamation of agricultural lands , and thus the expansion of agriculture . this leads to an increase in production and the revitalization of agricultural-based industries , which contributes to economic growth , an increase in livestock , and paves the way for the development of domestic tourism , all of which requires a lot of labor and water , even for ablution and wadhing .contributes to eliminating unemployment . lt is noteworthy that the holy quran and the noble prophets sunnah emphasize rationalizing consumption .